Isma'ili modern : globalization and identity in a Muslim community - Steinberg, Jonah (Islamic civilization & Muslim networks., 2010)
The Isma'ili Muslims, a major sect of Shi'i Islam, form a community that is intriguing in its deterritorialized social organization. Informed by the richness of Isma'ili history, theories of transnationalism and globalization, and firsthand ethnographic fieldwork in the Himalayan regions of Tajikistan and Pakistan as well as in Europe, Jonah Steinberg investigates Isma'ili Muslims and the development of their remarkable and expansive twenty-first-century global structures. Led by a charismatic European-based hereditary Imam, Prince Karim Aga Khan IV, global Isma'ili organizations make a.